(untitled) (MAUSAM, 1976)
Regular weekly synoptic data of the stratospheric and mesospheric temperature, pressure wind over Thumba (Lat. 8032’N, Long. 760 52’E) have been obtained since 9 December 1970 using Soviet meteorological M-I oo rockets. Methods employed for processing the various types of data and their analysis procedure utilized in these Soviet meteorological rocket soundings are described. The preliminary processing of the radar and telemetry data is carried out manually, while the final data reduction is done by either Minsk-22 or IBM-360/44 computer. The ehaff wind data reduction method adopted in the piggy back fibre glass and copper chaff cloud experiments using M-I oo rockets is also explained briefly.